Monitoring Protein Secretion in Streptomyces Using Fluorescent Proteins - Hamed, Mohamed Belal; Vrancken, Kristof; Bilyk, Bohdan; Koepff, Joachim; Novakova, Renata; van Mellaert, Lieve; Oldiges, Marco; Luzhetskyy, Andriy; Kormanec, Jan; Anné, Jozef; Karamanou, Spyridoula; Economou, Anastassios (Frontiers in Microbiology, 2018)
Fluorescent proteins are a major cell biology tool to analyze protein sub-cellular topology. Here we have applied this technology to study protein secretion in the Gram-positive bacterium Streptomyces lividans TK24, a widely-used host for heterologous protein secretion biotechnology. Green and monomeric red fluorescent proteins were fused behind Sec (SPSec) or Tat (SPTat) signal peptides to direct them through the respective export pathway. Significant secretion of fluorescent eGFP and mRFP was observed exclusively through the Tat and Sec pathways, respectively. Plasmid over-expression was compared to a chromosomally integrated spSec-mRFP gene to allow monitoring secretion under high and low level synthesis in various media. Fluorimetric detection of SPSec-mRFP recorded folded states, while immuno-staining detected even non-folded topological intermediates. Secretion of SPSec-mRFP is unexpectedly complex, is regulated independently of cell growth phase and is influenced by the growth regime. At low level synthesis, highly efficient secretion occurs until it is turned off and secretory preforms accumulate. At high level synthesis, the secretory pathway overflows and proteins are driven to folding and subsequent degradation. High-level synthesis of heterologous secretory proteins, whether secretion competent or not, has a drastic effect on the endogenous secretome, depending on their secretion efficiency. These findings lay the foundations of dissecting how protein targeting and secretion are regulated by the interplay between the metabolome, secretion factors and stress responses in the S. lividans model.